Efficacy of Leptin Supplementation on Nuclear Maturation and Fertilization Rate of Sheep Oocytes In Vitro - A. Riyuska; N. W. K. Karja; A. Setiadi (Tropical Animal Science Journal, 2019)
The objective of this study was to determine the efficacy of leptin supplementation into maturation medium on nuclear maturation and fertilization rate of sheep oocytes. The maturation process was conducted using a tissue culture medium (TCM) 199 with four supplementation treatments of leptin namely 0 (control), 10, 50, and 100 ng/mL. Fertilization was conducted in the oocytes supplemented with 10 ng/mL and control using 5×106 mL-1 spermatozoa. At the end of maturation and fertilization processes, the oocytes were stained with 2% aceto orcein to determine nuclear maturation rate and pronuclear development. The results showed that the percentage of oocytes reaching metaphase II (MII) stage significantly increased in the oocytes supplemented with leptin at a dose of 10 ng/mL (P<0.05) compared to those supplemented at doses of 50, 100, and 0 ng/mL (93.7±5.9% vs 78.8±4.4%; 72.0±2.6%; 82.1±9.9%). However, fertilization rate of the oocytes supplemented with leptin at a dose of 10 ng/mL and control were similar (72.1±5.5% vs 79.2±7.0%). The data indicated that leptin could improve maturation rate in lower concentration. However, the improved maturation rate of oocytes with leptin supplementation at a dose of 10 ng/mL could not improve the fertilization rate of the oocytes. In conclusion, the supplementation of leptin at a dose of 10 ng/mL could increase the number of oocytes that reached MII stage, but could not increase the fertilization rate.